Kajian Teknis dan Ekonomis dalam Merencanakan Penggantian Alat Gali-Muat dan Angkut pada Penambangan Nikel Laterit PT Tonia Mitra Sejahtera Kecamatan Kabaena Tengah Kabupaten Bombana Provinsi Sulawesi Tenggara - A. Sulhan Dwi Wahyullah; Zaenal; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Abstract. The condition of mechanical which has almost reached the service life of the tool requent breakdowns, resulting in decreased machine performance and higher operating costs, of course, affects productivity and production which will decrease. Therefore it is necessary to replace the tool. In planning the replacement of mechanical equipment, it is necessary to conduct a technical and economical study. The technical study includes a study of equipment production, and an economic study includes operating costs, ownership costs, Present Worth Cost and Production Unit Cost values. The research method is taking primary data and also secondary data. Based on the results of technical and economic studies, the old excavating equipment with a production of 382.008.01 BCM/year and the new excavating equipment with a production of 443.071,00 BCM/year. While the old transporting production with production of 381,763.01 BCM/year and new transporting production of 441,953. 28 BCM/year. The cost of calculating the cost of Production Unit Cost for old excavating equipment is Rp. 4,657.94 BCM and New digging-loading equipment of Rp. 3.725,53 BCM. For the old transporting of the cost of Production Unit Cost Rp.2. 720.38 BCM and new transporting of Rp. 2.162,62 BCM. Based on technical and economic studies for excavating and transporting equipment needs to be replaced because the productivity of new tools is greater and operating costs are more efficient than old tools, from the results of Unit Cost Production for excavating and transporting new tools is more efficient than old tools, as well as long-term investment if buying new tools. Abstrak. Kondisi dari alat mekanis yang hampir mencapai batas umur pemakaian dan sering terjadi kerusakan, sehingga mengalami penurunan kinerja mesin dan biaya operasi alat semakin besar, tentunya mempengaruhi produktivitas dan produksi yang akan semakin menurun. Oleh karena itu maka perlu dilakukan penggantian alat. Dalam merencanakan penggantian alat mekanis maka perlu dilakukan kajian secara teknis dan ekonomis. Untuk kajian teknis meliputi kajian produksi alat, dan kajian ekonomis meliputi biaya operasi, biaya kepemilikan, nilai Present Worth Cost dan nilai Production Unit Cost. Metode penelitian dilakukannya pengambilan data primer dan data sekunder. Berdasarkan hasil kajian tekniks dan ekonomis, alat gali-muat lama dengan produksi sebesar 382.001,00 BCM/tahun dan alat gali-muat baru dengan produksi sebesar 443.071,25 BCM/tahun. Sedangkan alat angkut lama produksi dengan produksi sebesar 381.763,02 BCM/tahun dan alat angkut baru produksi sebesar 441.953,28 BCM/tahun. Biaya perhitungan biaya Production Unit Cost untuk alat gali-muat lama sebesar Rp. 4.657,94 BCM dan alat gali-muat baru yaitu sebesar Rp. 3.725,53 BCM. Untuk alat angkut lama biaya Production Unit Cost Rp.2.720,38 BCM dan alat angkut baru sebesar Rp.2.162,62 BCM. Berdasarkan kajian teknis dan ekonomis untuk alat gali-muat dan alat angkut perlu diganti karena produktivitas alat baru lebih besar dan biaya operasi lebih hemat dibandingkan alat lama, dari hasil Unit Cost Production untuk alat gali-muat dan angkut baru lebih hemat dibandingkan alat lama, serta investasi jangka panjang jika membeli alat baru.